2017
DOI: 10.1007/s11356-017-9482-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical-mediated degradation of diclofenac revisited: a computational approach to assessment of reaction mechanisms and by-products

Abstract: Advanced oxidation processes (AOPs) are based on the in situ production of hydroxyl radicals (•OH) and reactive oxygen species (ROS) in water upon irradiation of the sample by UV light, ultrasound, electromagnetic radiation, and/or the addition of ozone or a semiconductor. Diclofenac (DCF), one of the emerging organic contaminants (EOC), is of environmental concern due to its abundancy in water and is known to be subjected to AOPs. The current study uses density functional theory (DFT) to elucidate the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…for CLX, and this value is in good correlation with that reported in the literature obtained experimentally (0.65) [28,31].…”
Section: Toxicity Estimationsupporting
confidence: 91%
See 2 more Smart Citations
“…for CLX, and this value is in good correlation with that reported in the literature obtained experimentally (0.65) [28,31].…”
Section: Toxicity Estimationsupporting
confidence: 91%
“…The reactivity of cephalexin toward •OH is supposed to be either by hydrogen abstraction or hydroxyl addition. The concerned sites on cephalexin molecules are either hydrogen atoms, in which the outcome of their interaction with hydroxyl radicals is an abstraction reaction, or unsaturated carbon atoms, in which the result of their interaction with hydroxyl radicals is an addition reaction [28]. The reactivity of the candidate sites is studied through atom condensed Fukui index analysis.…”
Section: Initial Reaction Of CLX With •Ohmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclization product D 260 was detected and identified during DCF decomposition in UV/NO 3 – /HCO 3 – . This route was initiated by • OH-induced H-abstraction at C 8 as illustrated in SI Figure S17c. , The formed radical anion subsequently removed a chloride anion at C 6 via the dechlorination route to form a biradical under UV irradiation, which leads to a quick recombination with the generation of a five-membered cyclic product. Decarboxylation that led to the generation of D 216 , could be initiated with • OH-involved electron transfer on the carboxylic acid of the D 260 , which first formed a carboxylic radical, followed by removal of CO 2 and electron .…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is reported that the biological effects of some pharmaceuticals are changed by UV irradiation [6,7,8] on account of their photoconversion to photoproducts. Various photochemical reactions may be induced by UV irradiation [9,10,11]. These reports indicate that the generation of various photoproducts is dependent on these chemical reactions.…”
Section: Introductionmentioning
confidence: 99%